Quality of Life in Retirement: Health, Social, and Economic Dimensions - Meryem TEKİN EPİK (Yaşlı Sorunları Araştırma Dergisi, 2025)
This study examines the health, social and economic factors that influence the quality of life during the retirement period. In terms of health, retirement is associated with a decrease in physical activity and an increased risk of chronic diseases, both of which are significant concerns. However, maintaining an active lifestyle, following a balanced diet, and fostering social interactions play a crucial role in preserving and enhancing individuals’ health. From a social perspective, although retirement may weaken professional relationships, it offers opportunities to strengthen family and community ties. Economically, the adequacy of pension income and the availability of alternative income sources are critical for maintaining financial independence and ensuring continued social participation. Within the context of increasing life expectancy and evolving labor market dynamics, bridge employment and alternative income sources have become key components of postretirement financial security. Moreover, the rising demand for long-term care services due to the aging population present a significant economic burden. Consequently, many countries are shifting towards community-based care models to make these services more accessible and costeffective. To achieve a succesful retirement period, it is essential to improve access to healhcare services, expand social support systems, and develop sustainable financing models. Proper management of the retirement process enables individuals to experience a healthier, happier, and more productive later life.